Fundamentals of Entrepreneurship (ENT300) : Business Opportunity U-Laife Café / Nurul Izzah Mohamad Elly … [et al.] - Mohamad Elly, Nurul Izzah; Was, Nur Azlin; Jamal, Nurhaliza; Ahmad Nizam, Nur Ernaniza; Zinal Abidin, Nur Fatin Qirana (2019)
According to the some aspect, our group would like to develop a U-LAIFE Cafe business which is business of products and services oriented. U-LAIFE Cafe is based on the combination of Cafe and Bakery. The reason we develop the business because there are no franchise that provide the same products and services as the U-LAIFE Cafe and located at UITM Campus Samarahan 2.